Strategi Implementasi Manajemen Risiko Pembiayaan Pada KSPPS KSA “Kedung Salman Alfarizy” Jepara - Silfana, Nadia; Hazmi, Faiqul (Jurnal Iqtisaduna, 2024)
This research aims to explain the financing risk management strategy implemented by KSPPS KSA "Kedung Salman Alfarizy" Jepara. Sharia financing is increasingly in demand by various levels of society. This is in line with Sharia Microfinance Institutions (LKMS) which aim to provide financial services by Sharia principles to the public. Sharia Financing Savings and Loans Cooperative (KSPPS) is one of the institutions that offer financing on a micro-scale, providing financial support to individuals and businesses without violating Sharia principles. This research uses a qualitative approach from primary and secondary data with qualitative descriptive analysis techniques. This research concludes that preventive financing analysis steps are implemented based on the 5C principles: Character, Capacity, Capital, Collateral, and Economic Conditions. Apart from that, KSPPS KSA "Kedung Salman Alfarizy" Jepara implemented curative strategies such as monitoring, rescheduling, reconditioning, and restructuring to overcome problematic financing. To reduce the negative impact of problematic financing, it is important to empower the institution internally and provide education to members of KSPPS KSA "Kedung Salman Alfarizy" Jepara in maintaining a healthy organizational and financial balance.